Assessment and Development of Communicative Skills in English: A Case Study of 1st Year Undergraduate Students Learning English As Their Major - Ivanova, A.V. (2020)
This article discusses the unique experiences and methods of independent examination of the level of communicative (specifically receptive and productive) English language skills of the first year undergraduate students studying English as the first foreign language in a Russian university, who previously passed the Unified State Exam (USE) in English. The results analyzed came from the tests the students took at the beginning of their first academic year. This study attempts to lay the foundations for the transition to level-oriented learning or to introduce differentiation in groups where students’ levels range widely – from A1 to C1. The assessment of the English language proficiency of students studying Philology, Linguistics, Foreign Regional Studies, and Pedagogy was carried out in the format the B2 First Cambridge exam (FCE). The results of the assessment were used to analyze their level of language knowledge and language skills according to the Common European Framework of Reference for Languages: Learning, Teaching, Assessment (CEFR). A number of typical mistakes made by students were revealed, based on which the students as well as their teachers were offered a number of recommendations to improve each of the skills.